Steuerflucht und Steueroasen - Kai A. Konrad; Jost H. Heckemeyer; Christoph Spengel; Markus Leibrecht; Margit Schratzenstaller; Manfred Gärtner; Thiess Büttner; Carolin Holzmann (Wirtschaftsdienst, 2013)
Die Debatte über Offshore-Leaks und die sehr geringen Steuerzahlungen großer multinationaler Konzerne haben das öffentliche Interesse auf das Problem 'Steueroasen' gelenkt. Wenn Konzerne Steuersatzunterschiede zwischen verschiedenen Ländern ausnutzen, kann Steuergestaltung durchaus legal sein. Werden aber steuerpflichtige Einkommen von Privatpersonen nicht deklariert, ist das illegal. Maßnahmen dagegen können neben der Aufdeckung von Straftaten an verschiedenen Stellen ansetzen: bei den Steuersätzen, der Regulierungsintensität, der Bemessungsgrundlage und den Informationspflichten. Werden die bestehenden Steueroasen ausgetrocknet, kann dies allerdings dazu führen, dass sich in großen Staaten neue Steueroasen herausbilden. – – The current debate on tax planning has to distinguish between tax evasion and aggressive tax planning. While tax evasion is illegal and requires the enhanced exchange of information, measures against aggressive tax planning seem to be very complex and complicated. Tax havens' benefits from tax haven activities are inversely related to the intensity of competition among tax havens. Once the set of tax havens narrows, each havens' share of the business increases and its margins go up. This competition aspect makes initial successes easy but final success very difficult. Nevertheless, some authors argue that action against tax flight is inevitable. As tax flight is a multilateral phenomenon, coordinated initiatives by country groups appear particularly promising. Here the EU should be in the vanguard. Only automatic information exchange generates the transparency and leeway needed to eliminate income tax evasion and to permit countries to devise tax codes at their own discretion. Despite the European trend towards lower corporate taxes, an empirical analysis shows that German multinationals have increased their tax haven activities. Recent research suggests that this development might be explained by the increased usage of anti-tax avoidance measures by high-tax countries. The substitutive nature of different tax-avoidance schemes indicates that only a coordinated closing of loopholes for profi t shifting would reduce the demand for tax-haven operations significantly.
Keywords: H21; H24; H26; K42; 330; Steueroase; Steuerwettbewerb; Steuerflucht; Welt